(untitled) (GnosisWisdom, 2025)
The research was framed within: Determining the relationship between pro-environmental attitudes and environmental education in students of the Academic Program of Intercultural Bilingual Primary Education at a Public Higher Pedagogical Institute in Peru. The research was basic in nature, descriptive in level, and used a descriptive-correlational design. The population consisted of 300 students, and the sample comprised 85 initial teacher training students with voluntary acceptance and current enrollment and regular attendance in cycles I, III, and V. Students on medical leave were excluded. Non-probabilistic, intentional sampling was used. The instruments used were the pro-environmental attitudes questionnaire and the environmental education questionnaire. These instruments resulted from collaborative construction, drawing on diverse experiences such as those of Saza Quintero et al. (2021), who conducted a study on pro-environmental behavior and environmental knowledge in university students, and Carranza Gonzales (2022), on environmental education and awareness in higher education students. Content validity was established through the judgment of three experts dedicated to the field of environmental education, as well as methodological validity. Reliability was calculated using Cronbach’s alpha coefficient, which measures the internal consistency of the items, with a value of 0.832, indicating appropriate reliability for its application. The results showed that: the majority of students (60%) had a high pro-environmental attitude, while a minority (40%) had a medium pro-environmental attitude overall. It was also found that the majority presented a high pro-environmental attitude in both its anthropocentric (55.3%) and ecocentric (74.1%) dimensions. Similarly, it was evident that the majority of students presented a medium level of environmental education (47.1%). Finally, the correlation between pro-environmental attitude and environmental education is significant with a p-value of 0.000 < 0.05 and a score of 0.603*. Whereas: the correlation between pro-environmental attitudes in their Anthropocentric and Ecocentric dimensions with environmental education was significant (p < 0.000), with scores of 0.594* and 0.523* respectively, being significant in both cases. All of this allows us to highlight the importance of safeguarding environmental education as a key component in initial teacher training, especially in intercultural contexts, in order to promote practices and values oriented towards sustainability.